On the determinants of speculation - a case for extended disclosures in corporate risk management - Andreas Hecht (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We examine the determinants of corporate speculation and challenge the extant, conflicting evidence. Separating risk management (reducing currency-specific FX exposure) from speculation (increasing or holding currency-specific FX exposure constant), we provide unprecedented evidence that speculators are smaller, have more growth opportunities and possess lower internal resources than risk-managing firms. The refined granularity of our dataset stems from a unique regulatory environment, where a regulating authority recommends additional disclosures for FX risk management in excess of governing accounting standards. Our findings enable investors, henceforth, to identify speculation from public available sources, where our results substantiate the significance of such an extended reporting. Thus, this case of optional disclosures might serve as blueprint for further regulatory refinements in other settings.
urn:nbn:de:bsz:100-opus-13878
Keywords: G32; G38; G39; 330; Foreign Exchange; Risk Management; Selective Hedging; Speculation; Disclosure; Reporting